Economic Impacts of Climate Change on Florida: Estimates from Two Studies - Tatiana Borisova; Norman Breuer; Roy Carriker (EDIS, 2009)
FE787, a 12-page fact sheet by Tatiana Borisova, Norman Breuer, and Roy Carriker, focuses on one piece of the policy-making puzzle related to climate change: possible economic costs for the state of Florida associated with climate change projections. Includes references. Published by the UF Department of Food and Resource Economics, December 2008.